Ações do metil jasmonato sobre a inflamação e o estresse oxidativo sistêmicos em ratos com artrite induzida por adjuvante - Soni Neto, Jamil (2017)
Methyl jasmonate (MeJA) is a natural fatty acid-derived cyclopentanone which shares structural similarities with prostaglandins and therefore many studies have been carried out to evaluate their actions on mammal cells, specially the potential anti-inflammatory and anti-can-cer activities. MeJA was able to inhibit the proliferation in various murine and human cancer cell lines and the mitochondria seem to be the main target of MeJA action, which stimulates the production of reactive oxygen species (ROS), bind to and detach the mitochondria-bound hexo-kinase, ATP depletion and finally cell death. Regarding the anti-inflammatory action MeJA was able to inhibit NFκB -mediated production of nitric oxide, prostaglandin E, TNF-α, IL-1 and IL-6 in LPS-activated murine macrophages (RAW264.7). However, these effects have been demonstrated only in isolated cells and no study has until now evaluated if MeJA is able to inhibit in vivo the inflammation. The present study therefore investigated the action of MeJA on the systemic inflammation and oxidative status in rats with adjuvant-induced arthritis, an experimental pathology in rats that shares many features with the human rheumatoid arthritis. Arthritic animals present systemic inflammation and in addition to articular sites other organs are affected, such as liver, which presents marked metabolic alterations associated to a pro-nounced oxidative stress. The present study has also evaluated the actions of MeJA on ROS production and respiratory activity of hepatic isolated mitochondria. Finally, this study also investigated the effect of MeJA on hepatic hexokinase (glucokinase) activity, enzyme that cat-alyzes the first rate-limiting step of glycolysis, which is reported to be accelerated in the arthritic liver. The arthritis induction was performed in Holtzman rats with Freund's adjuvant. Animals were distributed into seven groups: controls (healthy), which received corn oil; controls treated with 300 mg·Kg-1 MeJA; arthritic rats, which received corn oil; arthritic rats treated with 75, 150 and 300 mg·Kg-1 MeJA; and arthritic rats treated with 30 mg·Kg-1 ibuprofen. The treatment was made orally (gavage) once a day for 5 days prior to arthritis induction and by additional 18 days after. Paw volume was measured by plethysmography and the score of secondary lesions was assessed from the 10th to 18th day. Circulating leukocytes and those recruited into the fem-orotibial joint cavities were further quantified in the arthritic rats. At day 19th, peritoneal cavity of anesthetized rats was exposed, the blood was collected from the cava vein and the liver was removed to perform mitochondria isolation and homogenate preparation. Protein carbonyl groups, TBARS and ROS were measured in the homogenate to evaluate the liver oxidative stress. Oxidized (GSSG) and reduced (GSH) glutathione contents and activity of the enzymes catalase, SOD, myeloperoxidase (MPO) and glucokinase were measured in the homogenate supernatant. The ferric reducing ability of plasma (FRAP), thiol groups, albumin, protein car-bonyl groups and the activities of MPO, AST, ALT and alkaline phosphatase were measured in the plasma. Mitochondria were isolated by differential centrifugation and used to measure real time ROS production and respiratory activity. Mitochondrial respiration was measured in the presence (state III) and absence (basal and state IV) of ADP and activities of the NADH and succinate oxidases were measured in disrupted mitochondria. ROS production and respiratory activity were measured in isolated hepatic mitochondria incubated with MeJA exogenously added in the range up to 10 mM and also in mitochondria isolated from animals treated with MeJA. Arthritic rats developed an intense inflammatory response to adjuvant in both injected and contralateral paws. Animals furthermore presented very low body weight gain and systemic inflammatory manifestations, as evidenced by higher plasma and liver MPO activity, low levels of plasma albumin, severe secondary lesions to arthritis and higher number of total leukocytes in the blood and also recruited into the femorotibial joint cavities. Oxidative stress was also pronounced in the plasma and liver of arthritic rats, as evidenced by higher levels of ROS, TBARS and protein carbonyl groups, as well as decreased activity of catalase and GSH/GSSG ratio in the liver, whereas higher levels of protein carbonyl groups and decreased FRAP and thiols were verified in the plasma. Injected and non-injected paw volumes were respectively 55% lower and not altered in arthritic rats treated with 300 mg·Kg-1 MeJA, which also decreased the number of total leukocytes in the blood and recruited into the femorotibial joints. However, score of secondary lesions and plasma albumin levels in arthritic rats were not modified by MeJA treatment. MPO activities in the plasma and livers were respectively 40 and 27% lower in arthritic rats treated with 300 mg·Kg-1 MeJA. Treatment of control and arthritic rats with MEJA did not modify the AST, ALT and phosphatase alkaline activities in the plasma. MeJA (150 and 300 mg·Kg-1) abolished the increase of carbonylated proteins in the plasma and liver, and ROS content in the liver, and decreased (only 300 mg·Kg-1) the hepatic GSH/GSSG ratio and catalase activity in arthritic rats. In addition, MeJA increased FRAP and thiols groups in the plasma. MeJA exogenously added (1.25-10 mM) stimulated ROS production and inhibited respiration in isolated hepatic mitochondria of control and arthritic rats, but only mitochondrial ROS production was stimulated when rats were treated with MeJA (300 mg·Kg-1). The activi-ties of NADH and succinate oxidases were inhibited in isolated hepatic mitochondria by MeJA exogenously added and also in arthritic and control rats treated with 300 mg·Kg-1 MeJA. He-patic glucokinase activity was 60% higher in arthritic rats (compared to the controls) and treat-ment of control (only 300 mg·Kg-1) and arthritic rats with MeJA (all doses) inhibited the glu-cokinase activity by approximately 60%. MeJA was effective as an anti-inflammatory agent, particularly at the dose of 300 mg·Kg-1, which was able to decrease the paw edema, leukocytosis and leukocytes recruitment into the femorotibial joints, actions that were similar to ibuprofen, a classical anti-inflammatory drug. The mechanism of MeJA action seems to be associated with inhibition of NFκB -induced ex-pression and release of cytokines. Pronounced oxidative stress in the plasma of arthritic rats occurs as consequence of low levels of albumin and thiol groups. Only this last was improved by the remission of inflammation, but it was enough to decrease the plasma oxidative stress. Regarding the liver, oxidative stress is more pronounced as consequence of an impaired ROS scavenging system associated with increased production of ROS, which are induced by proin-flammatory cytokines directly and indirectly by stimulating the liver oxidative metabolism. In fact, the accelerated glycolysis in the liver of arthritic rats lead to an increased flux of reducing equivalents from the cytosol to mitochondria, making the cytosol more oxidized. MeJA was able to diminish the oxidative stress in the liver of arthritic rats, an effect that seems to be the consequence of both a suppression of the cytokine-induced pro-oxidant system and an improve-ment of the antioxidant defense, particularly the GSH/GSSG ratio. Although MeJA has also stimulated production of ROS in the liver mitochondria of arthritic rats, oxidative stress was not modified in the organ, a phenomenon that could be associated to a diminished flux through the glycolysis due to glucokinase inhibition. The effective doses of MeJA in the present study may be still relatively high, but they had no toxic effects and make this compound a potentially important starting point for anti-inflammatory and anti-rheumatic drugs development.